Islam, Alcohol, and Identity: Towards a Critical Muslim Studies Approach. (1st April 2018) - ,; ,
Abstract : Framed in a critical Muslim studies approach, this article offers a new understanding of the Ḥanafī position on alcohol, following major public debates on the question of alcohol sparked by prominent members of Al-Azhar University (Egypt) in 2012. Close textual analysis of a range of primary sources in Arabic and Urdu are foundational to the article, as are the categorisation and contextualisation of Ḥanafī discourse. This is all but a starting point, however, for an argument that constitutes a radical break from conventional Islamic studies, seen as "normal science, " in its critique of hegemonic discourses which have essentialised Islam on the basis of specific ontic manifestations, such as the prohibition of alcohol.